Economics of small-scale aquaculture farms in Brazilian Northeastern semi-arid region: Characteristics, feasibility, and profitability models - Vinícius Fellype Cavalcanti de França; Luis Otávio Brito da Silva; Emerson José da Silva Oliveira; Humber Agrelli de Andrade (Aquaculture and Fisheries)
Inland aquaculture represents a significant component of the aquaculture sector in Brazil. This activity is present in all Brazilian regions, yet the economic feasibility and the relationship between their productive variables and profitability indices remain poorly accessed in Brazil's semi-arid regions. This study aims to characterise, assess the economic feasibility, and evaluate the relationship between productive variables and profitability indices in the aquaculture sector in Feira Nova (Northeast Brazil). The data was collected through interviews with all producers in Feira Nova city and modelled using the software R. The aquaculture sector in Feira Nova is predominantly small-scale and encompasses a wide range of production strategies for shrimp and fish cultures, with profitable outcomes. The models demonstrated that economic and management variables were more closely associated with profitability indices than farm characteristics such as farm size. Feira Nova's profitability indices reinforces the small-scale aquaculture as a promising activity to alleviate poverty and generate wealth in Brazil semi-arid regions. However, governance improvements are necessary to boost the development of inland aquaculture in the country.